2022
DOI: 10.1039/d2ra03474c
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a graphene-based sensor to detect the humidity and the temperature of a metal body with imprecise data analysis

Abstract: Graphene is a 2D material with remarkable properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The classical graphs only define the variation against a single value, but the neutrosophic graphs show the variation of the whole interval. Therefore, as a result, it can be concluded that the neutrosophic approach is flexible, informative, and reliable in the analysis of sensing data. , …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The classical graphs only define the variation against a single value, but the neutrosophic graphs show the variation of the whole interval. Therefore, as a result, it can be concluded that the neutrosophic approach is flexible, informative, and reliable in the analysis of sensing data. , …”
Section: Resultsmentioning
confidence: 97%
“…Therefore, as a result, it can be concluded that the neutrosophic approach is flexible, informative, and reliable in the analysis of sensing data. 18 , 29 …”
Section: Resultsmentioning
confidence: 99%
“…The structure of the graphene thin film was studied using the XRD technique, 18 and the XRD pattern can be seen in Fig. 1(a) .…”
Section: Resultsmentioning
confidence: 99%
“…If we talk about the sensors the fabrication or best material for the sensors, according to our best graphene (due to novel structure and other properties [ 16 ]) based temperature [ 17 , 18 ], pressure [ 19 ] and humidity [ 20 ] sensors are more effective than other materials. Future more, if we talk about sensors data analysis one can use different statistic approaches as we have worked in our previous works [ [21] , [22] , [23] ].…”
Section: Complex Wireless Sensors Model (Cwsm)mentioning
confidence: 99%